Financial Regulation, Climate Change, and the Transition to a Low-Carbon Economy : A Survey of the Issues - Demekas, Dimitri (IMF Working Papers; Working Paper ;, 2021)
There are demands on central banks and financial regulators to take on new responsibilities for supporting the transition to a low-carbon economy. Regulators can indeed facilitate the reorientation of financial flows necessary for the transition. But their powers should not be overestimated. Their diagnostic and policy toolkits are still in their infancy. They cannot (and should not) expand their mandate unilaterally. Taking on these new responsibilities can also have potential pitfalls and unintended consequences. Ultimately, financial regulators cannot deliver a low-carbon economy by themselves and should not risk being caught again in the role of 'the only game in town.'